Subacute sclerosing panencephalitis with bilateral inferior collicular hyperintensity on magnetic resonance imaging brain - Thomas, Maya (Medknow Publications & Media Pvt Ltd, 2012)
Subacute sclerosing panencephalitis (SSPE) is chronic encephalitis occurring after infection with measles virus. An 8-year-old boy presented with progressive behavioral changes, cognitive decline and myoclonic jerks, progressing to a bed bound state over 2 months. Magnetic resonance imaging (MRI) brain showed T2-weighted hyperintensities in the subcortical areas of the left occipital lobe and brachium of the inferior colliculus on both sides. EEG showed bilateral, synchronous periodic discharges. Serum/cerebrospinal fluid measles IgG titer was significantly positive. The overall features were suggestive of SSPE. MRI finding of bilateral inferior colliculus changes on MRI without significant involvement of other commonly involved areas suggests an uncommon/rare imaging pattern of SSPE.